Kurikulum Pendidikan Luar Sekolah - Ade Putri Muliya (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2022)
The curriculum is one of the important aspects in educational activities. The out-of-school education curriculum is a set of rules and plans that regulate out- of-school educational activities whose implementation is more emphasized on providing expertise or skills in a particular field in order to live in accordance with the times and increasingly advanced science and technology. The difference between out-of-school education and school education is the legitimacy or formalization of education. In addition, the curriculum in out-of-school education is more flexible and in its preparation the community participates. The components of the out-of-school education curriculum consist of objectives, content, strategies/methods, and evaluation of activities.